El Occidente islámico en la historiografía mameluca del período baḥrī (648-784/1250-1382). Fuentes y recepción de la historia de al-Andalus - Padillo-Saoud, Abdenour (Medievalista, 2025)
Referencias bibliográficas Estudios BANISTER, Mustafa – The Abbasid Caliphate of Cairo, 1261-1517. Edimburgo: Edinburgh University Press, 2021. BERKEY, Jonathan – The Formation of Islam. Religion and Society in the Near East, 600-1800. Nueva York: Cambridge University Press, 2003. IRWIN, Robert – The Middle East in the Middle Ages: The Early Mamluk Sultanate 1250-1382. Illinois: Southern Illinois University Press, Beckenham, 1986. LEVANONI, Amalia – “The Mamlūks in Egypt and Syria: the Turkish Mamlūk Sultanate (648-784/1250-1382) and the Circassian Mamlūk Sultanate (784-923/1382-1517)”. In FIERRO, Maribel (ed.) – The New Cambridge History of Islam. Vol. 2. Cambridge: Cambridge University Press, 2010, pp. 237-284. MOLINA, Luis – “Técnicas de amplificatio en el Muqtabis de Ibn Hayyan”. Talia Dixit 1 (2006), pp. 55-79. MUHANNA, Elias – Encyclopaedism in the Mamluk Period: The composition of Shihāb Al-Dīn Al-Nuwayrīʾs (D. 1333). Nihāyat Al-Arab Fī Funūn Al-Adab. Cambridge, Massachusetts: Harvard University, 2012. Tesis doctoral, pp. 39-47. MUHANNA, Elias – The World in a Book. Al-Nuwayri and the Islamic Encyclopedic Tradition. Princeton, NJ: Princeton University Press, 2018. PADILLO-Saoud, Abdenour – “La historia de los omeyas de al-Andalus en el enciclopedismo mameluco. Un análisis historiográfico de la Nihāyat al-arab y los Masālik al-abṣār”. Al-Qanṭara 43:2 (2022), e 27. Proyecto AMOI-I, https://www.eea.csic.es/eea-proyectos-de-investigacion/contextos-locales-y-dinamicas-globales-al-andalus-y-el-magreb-en-el-oriente-islamico-amoi/ Proyecto AMOI-II, https://www.eea.csic.es/eea-proyectos-de-investigacion/al-andalus-y-el-magrib-en-el-oriente-islamico-movilidad-migracion-y-memoria-amoi-ii/ VAN STEENBERGEN, Jo y TERMONIA, Maya (eds.) – New Readings in Arabic Historiography from Late Medieval Egypt and Syria. Proceedings of the Themed Day of the Fifth Conference of the School of Mamluk Studies. Leiden, Boston: Brill, 2021.